Treatment of Metastatic Colorectal Cancer: ASCO Guideline. Issue 3 (17th October 2022) - Morris, Van K.; Kennedy, Erin B.; Baxter, Nancy N.; Benson, Al B.; Cercek, Andrea; Cho, May; Ciombor, Kristen K.; Cremolini, Chiara; Davis, Anjee; Deming, Dustin A.; Fakih, Marwan G.; Gholami, Sepideh; et al.
Abstract : PURPOSE: To develop recommendations for treatment of patients with metastatic colorectal cancer (mCRC). METHODS: ASCO convened an Expert Panel to conduct a systematic review of relevant studies and develop recommendations for clinical practice. RESULTS: Five systematic reviews and 10 randomized controlled trials met the systematic review inclusion criteria. RECOMMENDATIONS: Doublet chemotherapy should be offered, or triplet therapy may be offered to patients with previously untreated, initially unresectable mCRC, on the basis of included studies of chemotherapy in combination with anti–vascular endothelial growth factor antibodies. In the first-line setting, pembrolizumab is recommended for patients with mCRC and microsatellite instability-high or deficient mismatch repair tumors; chemotherapy and anti–epidermal growth factor receptor therapy is recommended for microsatellite stable or proficient mismatch repair left-sided treatment-naive RAS wild-type mCRC; chemotherapy and anti–vascular endothelial growth factor therapy is recommended for microsatellite stable or proficient mismatch repair RAS wild-type right-sided mCRC. Encorafenib plus cetuximab is recommended for patients with previously treated BRAF V600E–mutant mCRC that has progressed after at least one previous line of therapy. Cytoreductive surgery plus systemic chemotherapy may be recommended for selected patients with colorectal peritoneal metastases; however, the addition of hyperthermic intraperitoneal chemotherapy is not recommended. Stereotactic body radiation therapy may be recommended following systemic therapy for patients with oligometastases of the liver who are not considered candidates for resection. Selective internal radiation therapy is not routinely recommended for patients with unilobar or bilobar metastases of the liver. Perioperative chemotherapy or surgery alone should be offered to patients with mCRC who are candidates for potentially curative resection of liver metastases. Multidisciplinary team management and shared decision making are recommended. Qualifying statements with further details related to implementation of guideline recommendations are also included. Additional information is available at www.asco.org/gastrointestinal-cancer-guidelines .